Nicotine Acutely Enhances Reinforcement from Non-Drug Rewards in Humans - Perkins, Kenneth A.; Karelitz, Joshua L.; Boldry, Margaret C. (Frontiers in Psychiatry, 2017)
Preclinical research documents that, aside from the primary and secondary reinforcing effects of nicotine intake itself, nicotine also acutely enhances the reinforcing efficacy of non-drug reinforcers (“rewards”). Study of these effects in humans has largely been overlooked, but very recent findings suggest they may have clinical implications for more fully understanding the persistence of tobacco dependence. This overview first outlines the topic and notes some recent human studies indirectly addressing nicotine effects on related responses (e.g. subjective ratings), explaining why those findings do not directly confirm enhancement of behavioral reinforcement per se due to nicotine. Then, the methodology used in the subsequently presented studies is described, demonstrating how those studies specifically did demonstrate enhancement of reinforced responding for non-drug rewards. The main section focuses on the limited controlled research to date directly assessing nicotine’s acute reinforcement enhancing effects in humans, particularly as it relates to reinforced behavioral responding for non-drug rewards in non-human animal models. After detailing those few existing human studies, we address potential consequences of these effects for dependence and tobacco cessation efforts and then suggest directions for future research. This research indicates that nicotine per se increases responding in humans that is reinforced by some rewards (auditory stimuli via music, visual stimuli via video), but perhaps not by others (e.g. money). These reinforcement enhancing effects in smokers are not due to dependence or withdrawal relief and can be restored by a small amount of nicotine (similar to a smoking lapse), including from e-cigarettes, a non-tobacco nicotine product. Future clinical research should examine factors determining which types of rewards are (or are not) enhanced by nicotine, consequences of the loss of these nicotine effects after quitting smoking, potential individual differences in these effects, and the possibility that nicotine via NRT and non-nicotine quit medications may attenuate loss of these effects upon quitting. Further study with humans of nicotine’s reinforcement enhancing effects may provide a more complete understanding of smoking persistence and added mechanisms of cessation medication efficacy.